Heart failure, exercise training and systemic inflammatory Insuficiência cardíaca, exercício físico e sistema inflamatório - Ulbrich A.Z.* (2015)
© Copyright Moreira Jr. Editora.Background: In the context of heart failure's (HF) treatment, it is important to better understand the consequences of interaction between exercise and inflammation, considering the strong influence of both in clinical course of the syndrome. Objective: Search for qualified information of the effects of physical exercise on inflammatory profile of patients with HF. Methods: The search for journals was held in databases CONCHRANE, PUBMED and LILACS. The following MeSH terms were used: heart failure, exercise and inflammatory mediators. The studies were selected by two reviewers and qualified according to criteria of the Delphi List. Results: Nineteen controlled clinical trials were selected. The studies were heterogeneous with regard to sport and physical exercise protocols used in the investigation of the effects on the behavior of inflammatory mediators, with emphasis on moderate intensity aerobic activity. The outcomes studies show chronicle reduction of proinflammatory cytokine of both cardiac and systemic action, as well as endothelial action and cell apoptosis due to physical exercise. No study assessed the influence of high intensity exercise on inflammatory markers. Conclusion: It has been demonstrated that physical exercise aerobically predominantly used with moderate provides stabilization and decreased pro-inflammatory markers, something desirable in the treatment of HF. No studies showing the effects of isolated resistance exercise, as well as the effect of high-intensity exercise on inflammatory markers in patients with HF.